2022
DOI: 10.1111/1460-6984.12750
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID‐19 on digital practice in UK paediatric speech and language therapy and implications for the future: A national survey

Abstract: Background:The COVID-19 pandemic and subsequent measures to reduce transmission risk has led to unprecedented digital transformation across health, education and social care services. This includes UK paediatric speech and language therapy (SLT), which sits at the crossroads of these services. Given the rapid onset of this pandemic-induced digital transition, there is now a need to capture, reflect and learn from the SLT profession so that benefits can be sustained, and barriers addressed. Aims: To survey the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…The outcomes indicated emerging trends in UK paediatric SLTs' perceptions of telehealth, and SLTs perceived that a hybrid approach to service delivery, combining mostly face-to-face services with some telehealth, was likely to continue in the future, supporting the findings of a similar national survey of paediatric SLTs (Patel et al, 2022).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The outcomes indicated emerging trends in UK paediatric SLTs' perceptions of telehealth, and SLTs perceived that a hybrid approach to service delivery, combining mostly face-to-face services with some telehealth, was likely to continue in the future, supporting the findings of a similar national survey of paediatric SLTs (Patel et al, 2022).…”
Section: Discussionsupporting
confidence: 59%
“…As telehealth services continue to develop, SLTs placed importance on managers addressing the practical impacts (both positive and negative) of telehealth on their organisation and practitioners' workload, and prioritising which activities telehealth is most practicable for. The importance of leadership at an organisation level for telehealth implementation was also highlighted in Patel et al (2022).…”
Section: Discussionmentioning
confidence: 99%
“…As highlighted by Patel et al. (2022), specialist training is essential for post‐pandemic telepractice and hybrid service delivery. Our study shows the need for support to develop expertise in identifying who can benefit from telepractice, including how to conduct assessments online, how to provide caregiver coaching and build relationships, as well as basic technical skills.…”
Section: Discussionmentioning
confidence: 99%
“…Grillo, 2017; Hines et al., 2015; Pitt et al., 2018) and during the COVID‐19 pandemic (e.g. Biggs et al., 2022; Hao et al., 2021; Kwok et al., 2022; McCaslin, 2021; Patel et al., 2022; Tambyraja et al., 2021) have been conducted in Global North settings. Given the difficulties related to telepractice provision identified in resource‐rich areas of the world, it is important to explore the experiences of SLTs working in contexts that already face barriers such as those related to technological access and internet connectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Other research has identified that SLTs employed changes to practice in the initial response to COVID-19 that were favourable and that they wish to maintain, for example an increase in use of telehealth and greater contact with service user's families (Morgan et al, 2023). A recent survey of practice of UK SLTs specifically explores the changes in practice around telehealth since COVID-19 and signals a positive shift in SLTs' recognition and acceptance of technology use in practice (Patel et al, 2022). Extending the scope of our survey to capture positive effects way would have strengthened the study and enriched the contribution through potentially offering new solutions that could be applied in clinical practice.…”
Section: Speech and Language Therapy After Covid-19mentioning
confidence: 99%